Effect of football size and mass in youth football head impacts - Dunn, M.; Davies, D.; Hart, J. (Proceedings, 2020)
In youth association football, the use of different size and/or mass footballs might represent a feasible intervention for addressing heading impact severity and player safety concerns. This study assessed the effects of football size and mass on head impacts based on defensive heading in youth football. Three-dimensional trajectories of U16 youth academy free kicks were modelled to derive three impact trajectories, representing defensive heading in youth football. Three football models (standard: S5, standard-light: S5L, and small: S4) impacted an instrumented headform; Head Injury Criterion (HIC15) and Rotational Injury Criterion (RIC15) were calculated. For headform impacts, S4 and S5L footballs yielded lower HIC15 magnitudes than S5 footballs. Further, S4 footballs yielded lower HIC15 and lower RIC15 magnitudes than S5 and S5L footballs. Initial findings indicated that smaller, S4 footballs reduced linear and rotational head injury criteria for impacts representative of defensive heading in youth football.